How to Grow Leaders the seven key principles of effective leadership development - Adair, John (London Kogan Page, 2005)
How to Grow Leaders is a ground-breaking book which sets the record straight on leadership development, the nature of leadership and how it can be taught. John Adair indentifies the seven key principles of leadership development, and answers vital questions on how to select, train and educate leaders at team, operational and strategic leadership levels. He discusses key topics such as : the manager as leader how people become leaders how to manage leadership training learning to be a strategic leader training team leaders Effective leadership is clearly a crucial factor in business success. How to Grow Leaders will help you to develop these skills in others, while guiding your own personal journey towards excellence as a leader
Includes index
Keywords: Leadership